Hybrid precoding with sub-connected architecture for millimeter wave massive MIMO system - Haiyan CAO; Xiaohui YANG; Wenjuan HU; Zichang MA; Fangmin XU; Xin FANG (Dianxin kexue)
A hybrid precoding scheme in the millimeter wave massive MIMO system was proposed with sub-connected architecture at the transmitter and digital combining at the receiver.In this scheme,the digital precoder and combiner were designed based on the singular value decomposition (SVD) of the equivalent channel matrix,while the optimal analog precoder was obtained by blocking the equivalent channel to maximize spectral efficiency according to the block diagonalization.Considering the hardware cost and power consumption,the precoding scheme with sub-connected architecture at the receiver was further proposed.Otherwise,the analog precoder and combiner were iteratively updated.Simulation results show that the proposed scheme which focuses on the digital combining at the receiver has better performance than successive interference cancelation (SIC)-based hybrid precoding.In addition,though the proposed scheme which focuses on the hybrid combining with sub-connected architecture at the receiver has worse performance than SIC-based hybrid precoding,the power consumption and hardware cost are greatly reduced.